Human rights, constitutional law and belonging the right to equal belonging in Democratic society - Drymiotou, Elena (Routledge research in human rights law, 2018)
While every constitution includes a provision over the right to equal protection of the laws, perhaps with different terminology, this book interprets this right in a new way. Theories of the right to equal protection of the laws as the right to anti-subordination are the most influential theories for the suggested one. However, they are not the same. Elena Drymiotou suggests to understand the right to equal protection of the laws right in terms of belonging. She goes on to identify certain criteria and she offers a general theory of the Right to Democratic Belonging. This book uses political theory, constitutional provisions, and case law to suggest this new theory of the right to equal protection of the laws; the theory of the Right to Equal Belonging in a Democratic Society or in other words, the Right to Democratic Belonging. It is the starting point of a more comprehensive theory of the right to democratic belonging. It will be of interest both to students at an advanced level, academics and reflective practitioners. It addresses the topics with regard to human rights and equality and will be of interest to researchers, academics, policymakers, and students in the fields of human rights law, constitutional law, and legal theory